2008
DOI: 10.1017/s1751731108002565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing system and mixing at loading on transport and lairage behaviour and meat quality: comparison of free range and conventionally raised pigs

Abstract: Free range pigs, born outdoors and reared after weaning in enriched indoor accommodation, were compared with conventionally raised pigs from a farm, matched for effects on meat quality, with respect to behaviour during transport and lairage, blood chemistry at slaughter and meat quality characteristics. Pigs were either kept in farm pen groups or were mixed at loading and kept in the groups, so formed, until slaughter. Free range pigs tended to settle faster during the 2 1 2 h transport and 2 h lairage than co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
(22 reference statements)
4
10
1
Order By: Relevance
“…No differences were found in blood cortisol concentration for pigs reared in outdoor and indoor systems (Rudine et al, 2007), or between both plasma and urine cortisol after transport and lairage for pigs reared in outdoor and indoor conventional system (Lebret et al, 2006). Similar results are reported by (Barton Gade, 2008) for free range and conventional raised pigs. However, the upholding of the differences showed at the farm between T1 and T2 after transport, as well as the higher level of aggression in T1 and the higher level of glucose, could be an evidence of distress in pigs under this treatment.…”
Section: Physiological Parameters 43supporting
confidence: 76%
“…No differences were found in blood cortisol concentration for pigs reared in outdoor and indoor systems (Rudine et al, 2007), or between both plasma and urine cortisol after transport and lairage for pigs reared in outdoor and indoor conventional system (Lebret et al, 2006). Similar results are reported by (Barton Gade, 2008) for free range and conventional raised pigs. However, the upholding of the differences showed at the farm between T1 and T2 after transport, as well as the higher level of aggression in T1 and the higher level of glucose, could be an evidence of distress in pigs under this treatment.…”
Section: Physiological Parameters 43supporting
confidence: 76%
“…However, when data were split according to the type of the UO, control pigs as well as non-hernia UO-pigs showed a higher frequency of aggression than the UO-pigs with umbilical hernia. For pigs, the normal post-mixing behaviour is fighting in order to re-establish the social hierarchy (Spoolder et al, 2000;Barton Gade, 2008), and so the lowered aggression level in UO-pigs as compared to control animals is a deviation from normal behaviour. This might be due to pain from the outpouchings or the animals attempting to avoid fighting-induced damage to their outpouchings.…”
Section: P-valuementioning
confidence: 99%
“…fasting (Gispert et al, 2000), mixing with unknown conspecifics (Barton Gade, 2008) and high stocking density (Warriss et al, 1998), which all may compromise animal welfare (Lambooij, 2007). However, effects of typical pre-slaughter stressors on pigs with umbilical outpouchings (OUs) have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions are prevalent welfare outcomes of mixing [ 9 , 10 ] and skin lesions measured on the carcass are suggested as more sensitive indicators of aggressiveness than those measured on the live pig [ 11 ]. Barton Gade and colleagues [ 12 ] found that the carcasses of pigs from mixed groups had a higher skin lesion score than those kept in static groups. Fighting increases plasma cortisol levels [ 8 ] and higher skin lesion scores are associated with higher plasma cortisol [ 13 ].…”
Section: Introductionmentioning
confidence: 99%